The efficacy and safety of Chinese herbal medicine for mild cognitive impairment: a systematic review and meta-analysis of randomized placebo-controlled trials - Liu, Lingling; Zhang, Claire Shuiqing; Zhang, Anthony Lin; Cai, Yefeng; Xue, Charlie Changli (Frontiers in Pharmacology, 2024)
Objective: Effective and safe treatments for mild cognitive impairment (MCI) are limited. Chinese herbal medicine (CHM) is commonly used in China to manage MCI. However, its efficacy and safety remain uncertain. This review aims to evaluate the efficacy and safety of CHM for MCI. Methods: Nine databases were searched from their inceptions to January 2023. Randomized, placebo-controlled trials of oral CHM for MCI were included. Study quality was assessed using the Cochrane risk-of-bias tool 2.0, and the certainty of evidence was evaluated via the GRADE approach. Results: Thirteen studies, involving 1,043 participants, were analyzed. Most of the studies (10 out of 13) were associated with ‘some concerns’ regarding the overall risk of bias. Meta-analyses results indicated that CHM significantly improved cognitive function compared to placebo in terms of Mini-Mental State Examination (MMSE) (MD: 1.90 [1.22, 2.58], I2 = 87%, 11 studies, 823 participants) and Montreal Cognitive Assessment (MoCA) (MD: 2.88 [1.69, 4.06], I2 = 81%, 3 studies, 241 participants). The certainty of evidence for MMSE was assessed as ‘moderate’, while it was ‘low’ for MoCA. One study did not report adverse events (AEs), one study reported no statistical difference between the groups in terms of AEs, and 11 studies provided detailed numbers of AE cases where gastrointestinal symptoms were the most commonly reported AEs. Two studies reported no SAEs among participants and one study found no significant difference in SAEs proportions between groups. The meta-analysis revealed no significant differences in AEs between the two groups (RR: 1.31 [0.92, 1.87), I2 = 0 %, 11 studies, 839 participants). The cognitive-enhancing function of commonly used herbs (Panax ginseng C.A.Mey., Acorus calamus var. angustatus Besser, and Polygala tenuifolia Willd.) may be attributed to mechanisms including antioxidant, anti-apoptotic, anti-neurotoxic, anti-cytotoxic, and anti-inflammatory actions. Conclusions: Chinese herbal medicine holds potential as an effective intervention to improve cognitive function in MCI patients, supported by meta-analyses evidence of low to moderate certainty. Although current data suggests CHM is generally safe, caution is advised due to the lack of AE reporting or detailed information in some instances. Systematic review registration: https://www.crd.york.ac.uk/prospero/, identifier [CRD42023400292].